Europe's climate policy – after Paris comes the harder part - Buchan, D (Oxford Institute for Energy Studies, 2017)
The Paris climate agreement is a big comfort to the European Union. The fact that so many governments have come forward with at least some form of emission reduction plan leaves the EU feeling less lonely in the fi ght against climate change and less exposed to competitive threats from economies with no carbon constraints.